Peptidome Analysis Reveals Novel Serum Biomarkers for Children with Autism Spectrum Disorder in China. Issue 5 (30th May 2018) - Yang, Juan; Chen, Yanni; Xiong, Xiaofan; Zhou, Xiaobo; Han, Lin; Ni, Lei; Wang, Wenjing; Wang, Xiaofei; Zhao, Lingyu; Shao, Dongdong; Huang, Chen
Abstract : Purpose: Autism spectrum disorder (ASD) is a neurological and developmental disorder that begins early in childhood and lasts throughout one's life. Early diagnosis is essential for ASD since early treatment can enable children with ASD to make significant gains in language and social skills, but remains challenging since there are currently no specific biomarkers of ASD. This study is aimed to identify serum biomarkers for ASD. Experimental design: Serum of Han Chinese children with ASD ( n = 68) and age‐matched healthy controls ( n = 80) is analyzed using magnetic bead–based separation combined with mass spectrum. Results: Eight potential ASD serum biomarker peaks ( m / z : 3886.69, 7775.12, 2381.71, 6638.63, 3319.17, 894.34, 4968.59, and 5910.53) with higher expression in ASD group are further identified as peptide regions of plasma serine protease inhibitor precursor (SERPINA5), platelet factor 4 (PF4), fatty acid binding protein 1(FABP1), apolipoprotein C‐I precursor (APOC1), alpha‐fetoprotein precursor (AFP), carboxypeptidase B2 (CPB2), trace amine‐associated receptor 6 (TAAR6), and isoform1 of fibrinogen alpha chain precursor (FGA). The expression of identified proteins is validated by enzyme‐linked immunosorbent assay (ELISA). Conclusions and medical relevance: These findings reveal the exceptional disease etiology of ASD from a serum proteomic perspective, and the identified proteins might be potential biomarkers for ASD diagnosis.